An Assessment of the Investment Climate in Botswana, Volume 2. Detailed Results and Econometric Analysis - World Bank (Washington, DC, 2012)
The objective of the Botswana Investment Climate Assessment (ICA) is to evaluate the investment climate in Botswana in all its operational dimensions and promote policies to strengthen the private sector. The investment climate is made up of the many location specific factors that shape the opportunities and incentives for firms to invest productively, create jobs, and expand. These factors include macroeconomic and regulatory policies; the security of property rights and the rule of law; and the quality of supporting institutions such as physical and financial infrastructure. The main sources of information for the ICA are two firm-level surveys. The first survey covered Small, Medium, and Large Enterprises (SMLEs) with five or more employees in retail trade, manufacturing, and other services. The second covered micro enterprise with fewer than five employees in the same sectors. Information from the survey is supplemented with information from other sources, including the doing business report; analytical reports by the World Bank, the international monetary fund, other international organizations and the Government of Botswana; and academic papers and reports. Although the analysis in this report suggests that there are some areas where the investment climate might be improved, it is important to note none of these problems with the possible exception of worker skills appear to be particularly debilitating. This suggests that other factors are probably also playing a role. One such factor is likely to be the small size (in terms of population) and remoteness of the economy. Another factor is the effect that is the macroeconomic effects of the large mining economy has on the competitiveness of the rest of the economy. Improving living standards and cutting poverty depends on broad-based economic growth, which will only take place when firms improve worker productivity by investing in human and physical capital and technological capacity. But firms will only invest when the investment climate is favorable.